Potensi Antiinflamasi Ekstrak dan Fraksi n-Heksana Daun Galam (Melaleuca cajuputi) Asal Kalimantan Selatan - Sutomo, Sutomo; Arnida, Arnida; Amalina, Amalina; Fadlilaturrahmah, Fadlilaturrahmah; Fitriana, Mia (Universitas Borneo Lestari, 2025)
South Kalimantan has a unique topography that includes tidal areas and swamps, and peatlands. One of the natural resources that grows well in this area is the galam tree (Melaleuca cajuputi). Traditionally, this plant has been used to treat various inflammatory conditions, such as intestinal inflammation, sore throat, itchy skin, and rheumatism. M. cajuputi contains flavonoid compounds that are believed to have anti-inflammatory properties. This study aimed to determine the anti-inflammatory activity of ethanol extracts and n-hexane fractions of M. cajuputi leaves from South Kalimantan using a protein denaturation inhibition method with IC50 values as the parameter. Sodium diclofenac was used as the positive control in this study. The results of the anti-inflammatory activity test showed that the IC50 values for sodium diclofenac, ethanol extract, and n-hexane fraction of M. cajuputi leaves were 14.948; 51.577; and 61.700 ppm, respectively. Statistical analysis revealed a significant difference between the IC50 value of sodium diclofenac and those of the ethanol extract and n-hexane fraction. Based on the study conducted, it can be concluded that the ethanol extract and n-hexane fraction have anti-inflammatory activity, although their potency is lower than that of sodium diclofenac